2022
DOI: 10.1136/bmjopen-2021-054833
|View full text |Cite
|
Sign up to set email alerts
|

Examining family planning and adverse pregnancy outcomes for women with active tuberculosis disease: a systematic review

Abstract: Objectives(1) Summarise and evaluate the current evidence of tuberculosis (TB)-associated pregnancy outcomes, (2) evaluate the state of the science of family planning during TB treatment and (3) provide recommendations to move forward to improve care and outcomes during TB disease.DesignSystematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines.Data sourcesPubMed, Embase, CINAHL, Cochrane, Web of Science and Scopus were searched from September 2009 to Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
0
4
1
Order By: Relevance
“…A systematic review of 69 studies (published 2009-2021), the majority of which were from low-income and middle-income countries, reported poor pregnancy outcomes for women with TB, with most studies reporting low birth weight and/or preterm labour and/or spontaneous abortions. 29 A South African study reported 48% of women routinely treated for multi-drug resistant/rifampicin resistant TB (MDR/RR-TB) during 2013-2017, had a poor pregnancy outcome, 30 higher than our study, where the majority had drug-sensitive TB. Other South African studies with cohorts between 2011 15 and 2014 14 showed that of infants born to HIVpositive mothers with TB, between 20% and 70% had a gestation period <37 weeks and between 21% and 59% had a low birth weight.…”
Section: Open Accesscontrasting
confidence: 62%
See 1 more Smart Citation
“…A systematic review of 69 studies (published 2009-2021), the majority of which were from low-income and middle-income countries, reported poor pregnancy outcomes for women with TB, with most studies reporting low birth weight and/or preterm labour and/or spontaneous abortions. 29 A South African study reported 48% of women routinely treated for multi-drug resistant/rifampicin resistant TB (MDR/RR-TB) during 2013-2017, had a poor pregnancy outcome, 30 higher than our study, where the majority had drug-sensitive TB. Other South African studies with cohorts between 2011 15 and 2014 14 showed that of infants born to HIVpositive mothers with TB, between 20% and 70% had a gestation period <37 weeks and between 21% and 59% had a low birth weight.…”
Section: Open Accesscontrasting
confidence: 62%
“…This finding should be interpreted with caution. Offering effective contraception to women at TB treatment initiation 29 36 and screening for pregnancy at each TB-related visit, with integration of reproductive health services as part of TB care is critical. 37 Women should be made aware of their increased risk of poorer pregnancy outcomes and need for additional care if they conceive during their TB episode.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account a higher rate of adverse SRH outcomes in HIV and TB co-infected women described in the literature and the elevated burden of both infections in women of reproductive age, it is important to continue strengthening proper screening, diagnosis, treatment and prevention of both conditions. Moreover, as the contraception use in this cohort was relatively low, the value of offering family planning to prevent adverse pregnancy outcomes in TB infected women has to be considered for the National TB Programs [ 25 ]. Counselling women about the risks associated with becoming pregnant while undergoing TB treatment and referring them to appropriate care if they intend to conceive is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women are at increased risk of developing TB, and this is associated with poor outcomes including premature birth, intrauterine growth retardation, and low birth weight. COVID-19 and tuberculosis co-infection in pregnancy is rare ( 1 , 8 ). In the general population, one study from China reveals the TB prevalence among COVID-19 patients ranged between 0.47 to 4.47% %.…”
Section: Discussionmentioning
confidence: 99%